Importance Employee Engagement And Position Promotion On Employee Performance In Small And Medium Business Groups In Banten Province - Hamdan, Hamdan (International Journal of Science, Technology & Management, 2022)
This study aims to determine the influence of Employee Engagement and Position Promotion on Employee Performance in Small and Medium Business Groups in Banten Province. The method used is a descriptive and associative quantitative method. The population of this research is employees with a sample of 81 people. Data was collected using a questionnaire. This study uses regression analysis using SPSS version 23 software Based on the results of hypothesis testing 1 shows employee engagement has a significant effect on employee performance. The results of hypothesis 2 test show that promotion has a significant effect on employee performance. The result of hypothesis test 3 shows that employee engagement and promotion have a positive and significant effect simultaneously on employee performance. The results of this study indicate that there is a significant influence between employee engagement and job promotion variables on employee performance by 3.2 %.